New Blind Muti-signature Schemes based on ECDLP - Duc Nguyen Tan; Hai Nguyen Nam; Minh Nguyen Hieu; Hiep Nguyen Van (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In various types of electronic transactions, including election systems and digital cash schemes, user anonymity and authentication are always required. Blind signatures are considered the most important solutions to meeting these requirements. Many studies have focused on blind signature schemes; however, most of the studied schemes are single blind signature schemes. Although blind multi-signature schemes are available, few studies have focused on these schemes. In this article, blind multi-signature schemes are proposed based on the Elliptic Curve Discrete Logarithm Problem (ECDLP). The proposed schemes are based on the GOST R34.10-2012 digital signature standard and the EC-Schnorr digital signature scheme, and they satisfy blind multi-signature security requirements and have better computational performance than previously proposed schemes. The proposed schemes can be applied in election systems and digital cash schemes.